Zinc Ion-Dependent Peptide Nucleic Acid-Based Artificial Enzyme that Cleaves RNABulge Size and Sequence Dependence - Murtola M; Ghidini A; Virta P; Stromberg R (MDPI AG, 2022)
In this report, we investigate the efficiency and selectivity of a Zn2+-dependent peptide nucleic acid-based artificial ribonuclease (PNAzyme) that cleaves RNA target sequences. The target RNAs are varied to form different sizes (3 and 4 nucleotides, nt) and sequences in the bulge formed upon binding to the PNAzyme. PNAzyme-promoted cleavage of the target RNAs was observed and variation of the substrate showed a clear dependence on the sequence and size of the bulge. For targets that form 4-nt bulges, we identified systems with an improved efficacy (an estimated half-life of ca 7-8 h as compared to 11-12 h for sequences studied earlier) as well as systems with an improved site selectivity (up to over 70% cleavage at a single site as compared to 50-60% with previous targets sequences). For targets forming 3-nt bulges, the enhancement compared to previous systems was even more pronounced. Compared to a starting point of targets forming 3-nt AAA bulges (half-lives of ca 21-24 h), we could identify target sequences that were cleaved with half-lives three times lower (ca 7-8 h), i.e., at rates similar to those found for the fastest 4-nt bulge system. In addition, with the 3-nt bulge RNA target site selectivity was improved even further to reach well over 80% cleavage at a specific site.